Archives of Anti-Colonial Resistance and the Liberation Struggle (AACRLS): An integrated programme to fill the colonial gaps in the archival record of Namibia (Journal for Studies in Humanities and Social Sciences, 2015)
National archives inherited from former colonial regimes suffer from a distorted record that marginalised the colonised people, and ignored or misrepresented their efforts for self-determination. The Archives was further depleted by the removal of vitally important records to the colonizing metropolis. As a result, the value of the archives as the memory of the entire nation is diminished. The article describes the efforts by the National Archives of Namibia to rectify this situation through a programme of repatriating or copying migrated, displaced and shared archives, collecting private records and oral history, and popularizing the history of anti-colonial struggles. It concludes that despite considerable successes, the task at hand is far from accomplished and needs further sustained effort.